Sustainability considerations in modeling and improvement of acid gas removal unit in gas processing plant - Noor Zulia, Bahaudin (2012)
Natural gas from wells contains significant amount of Hydrogen Sulfide and Carbon Dioxide which known as acid gas. Acid gas should be removed as the sulfur compound in hydrogen sulfide is extremely harmful and corrosive.The main process in Acid Gas Removal Unit(AGRU)is absorption, where the selection of the solvent is based on its capability to absorb or removing acid gas.Benfield Process is a chemical absorbing process by using Benfield solvent that consist of 30% Potassium Carbonate (K2CO3) ,water,DEA as activator and corrosion inhibitor.Solvent foaming is a contributor factor to the problem in the Benfield process due to degradation of DEA.The degradation will reduce the tendency of solvent absorption and also reduce the efficiency of absorption column.This research is carried out to simplify the AGRU process by reducing the number of equipment.A new simplified process has successfully constructed by replacing flash drum with a cooler to liquefied the solvent.Simulation using Aspen Hysys is then performed to study the modified process by using Peng-Robinson as property package.From the simulation on simplified PFD ,the capital cost of the process is reduced due to the reduction of equipment used in the process. Moreover, the objective of this research is to increase the efficiency of absorption process using Piperazine to replace DEA as activator in the Benfield solvent.As the conclusion, modified PFD with Piperazine in Benfield Solvent found can reduce the energy consumption, capital cost and give high efficiency absorption process.